India’s Balancing Act: Navigating Relations with Israel and Arab States Amidst Regional Tensions - Harsh Yadav (International Journal of Trends in Humanities, 2024)
India’s foreign policy in the Middle East represents a careful balancing act, showcasing its ability to manage long-standing relations with the Arab world alongside a growing partnership with Israel. India’s ties with Arab nations are grounded in shared historical, cultural, and anti-colonial links, especially in areas like trade and energy. Following independence, oil trade with the Gulf became vital for India’s energy needs, with strategic projects like the India-Middle East- Europe Economic Corridor further strengthening Indo-Arab cooperation. At the same time, since formally recognizing Israel in 1992, India has developed robust defence and technological exchanges with Israel, achieving key gains in agriculture and innovation. India's diplomatic difficulty in preserving neutrality while protecting its interests on both sides has been highlighted by navigating regional disputes like the Israel-Palestine and Israel-Iran confrontations. In order to foster communication and create bridges between opposing groups, India has also worked with international organizations like the Abraham Accords and the Organization of Islamic Cooperation (OIC). This study examines India's practical strategy for strengthening its position as a regional stabilizer by utilizing Israel's technological and defense breakthroughs while coordinating with Arab nations for economic and energy growth. The report examines how India's well-balanced diplomacy advances its strategic objectives and maintains its sway in a changing geopolitical environment, supporting its larger ambitions to become a major world power.
Keywords: India's Foreign Policy; diplomatic neutrality; energy trade; geopolitical strategy; middle east